A Switched Capacitor Memristor Emulator Using Stochastic Computing - Carola de Benito; Oscar Camps; Mohamad Moner Al Chawa; Stavros G. Stavrinides; Rodrigo Picos (Technologies, 2022)
Due to the increased use of memristors and their many applications, the use of emulators has grown in parallel to avoid some of the difficulties presented by real devices, such as variability and reliability. In this paper, we present a memristive emulator designed using a switched capacitor (SC), that is, an analog component/block and a control part or block implemented using stochastic computing (SCo) and therefore fully digital. Our design is thus a mixed signal circuit. Memristor equations are implemented using stochastic computing to generate the control signals necessary to work with the controllable resistor implemented as a switched capacitor.